2014
DOI: 10.14202/vetworld.2014.452-456
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of humoral immunity to Eimeria tenella sporozoites in chickens by ELISA

Abstract: Aim :Materials and Methods: Results:Conclusion:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, G4 showed no histopathological changes and showed normal intestines as chickens in G3. Similarly, Saravanan et al, (2014) found a destruction of cecal epithelium in all groups administered 10 and 20µg of live sporozoite antigen and Sharma et al, (2015) found coccidial oocysts in the intestine's lamina propria and the epithelial cells of the caecum's submucosal glands, massive infiltration of heterophils and mononuclear cells, together with desquamation and sloughing of enterocytes in the intestine resulted in intestinal villi necrosis, in addition to submucosal blood vessel congestion, fibrosis, and edema, as well as submucosal degeneration. Increased FCR and decreased BWG in G6 may be due to the presence of cecal lesion caused by E. tenella, which destroys the absorptive mucosal surface of the intestine (Logan et al, 1993;Kheirabadi et al, 2008;Marien and Gussem, 2007;Mathis et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…However, G4 showed no histopathological changes and showed normal intestines as chickens in G3. Similarly, Saravanan et al, (2014) found a destruction of cecal epithelium in all groups administered 10 and 20µg of live sporozoite antigen and Sharma et al, (2015) found coccidial oocysts in the intestine's lamina propria and the epithelial cells of the caecum's submucosal glands, massive infiltration of heterophils and mononuclear cells, together with desquamation and sloughing of enterocytes in the intestine resulted in intestinal villi necrosis, in addition to submucosal blood vessel congestion, fibrosis, and edema, as well as submucosal degeneration. Increased FCR and decreased BWG in G6 may be due to the presence of cecal lesion caused by E. tenella, which destroys the absorptive mucosal surface of the intestine (Logan et al, 1993;Kheirabadi et al, 2008;Marien and Gussem, 2007;Mathis et al, 2018).…”
Section: Discussionmentioning
confidence: 90%